The effects of economic migration of Poles for functioning of the family-selected aspects - Izabela Kochan (Studia z Teorii Wychowania)
About one billion people around the world move abroad or outside their birthplace seeking better earning possibilities. Economic migration has been accepted by many families as a strategy aiming improvement of their functioning. In a long-term prospect it affects the family’s well-being among others through investing in education and health. The mobility of one or several family members colours the leaving and those who remain at home both in positive and negative way depending individual conditions. Although postal orders are potentially an important way to mitigate the limits of the family budget, the weakest family members who need attention, repeatedly bear high cost of migration decisions. The individualistic effect of the economic migration of the Poles for functioning of their families is migrational orpanhood of the children and older people which is the main theme of intellectualizing in the present article. Special attention should be drawn to people in grand old age whose proportion in our country is still rising. In the context of relevant issues, it is necessary to take steps aiming to mitigate the costs of migration born by families, offering support recouping the losses coming from the mobility.